Pendidikan Islam dan Literasi Digital: Strategi Mengatasi Hoaks dan Konten Negatif di Kalangan Remaja Muslim - Ade Nurpriatna; Yanti Amalia Afifah; Neng Wina Shalehah (STAI Al-Mas'udiyah, 2025)
The rise of hoaxes and negative content on social media is a serious challenge that can affect the understanding of religion, morals, and psychology of adolescents. This study aims to analyze the role of Islamic Education in improving the digital literacy of Muslim adolescents and formulate effective strategies to overcome hoaxes and negative content. This study uses a qualitative approach with literature study methods and content analysis. Data was collected from sources such as the Qur'an, Hadith, books, journals, and articles related to digital literacy and Islamic Education. The results of the study show that Islamic education can be a moral and spiritual foundation in shaping adolescents' critical awareness of digital content. Islamic values such as tabayyun (verification), amanah (honesty), and hikmah (wisdom) can be integrated in digital literacy to fight hoaxes. The integration between Islamic Education and digital literacy is able to form a young generation of Muslims who are intelligent, critical, and responsible in social media. The synergy between religious values and digital skills is the key in facing the challenges of hoaxes and negative content in the digital era.